2006
DOI: 10.3758/bf03208757
|View full text |Cite
|
Sign up to set email alerts
|

The role of attention and familiarity in face identification

Abstract: How is attention allocated during face identification? Previous work using famous and unfamiliar faces suggests that either no attention or a special attentional mechanism is required. We used a conventional attentional blink (AB) procedure to measure face identification with temporarily reduced attention. The participants viewed a rapid series of face images with one embedded nonface abstract pattern (T1). They judged the texture of T1 and then detected a prespecified face (T2) presented at varying lags after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
85
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 81 publications
11
85
2
Order By: Relevance
“…This is somewhat surprising given the ; Jackson & Raymond, 2006;Shapiro, Caldwell, & Sorenson, 1997). As mentioned earlier, the skeletal AB task presents a straightforward test of the temporal resolution of the sustained use of limited capacity resources once target processing has been initiated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is somewhat surprising given the ; Jackson & Raymond, 2006;Shapiro, Caldwell, & Sorenson, 1997). As mentioned earlier, the skeletal AB task presents a straightforward test of the temporal resolution of the sustained use of limited capacity resources once target processing has been initiated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, targets with a degree of learnt salience, such as one's own name (Shapiro, Caldwell, & Sorenson, 1997), a famous face (Jackson & Raymond, 2006), or an emotionally salient word (Anderson, 2005;Anderson & Phelps, 2001) show a reduced impairment relative to more neutral stimuli. Similarly, when a stimulus that has been previously paired with an unpleasant outcome is used as a distractor in an RSVP task, it can automatically generate an impairment for subsequent targets, similar to that observed in the AB (Smith, Most, Newsome, & Zald, 2006).…”
Section: Timementioning
confidence: 99%
“…For instance, familiar or meaningful stimuli, such as one's own name (Shapiro, Caldwell, & Sorensen, 1997) or famous faces (Jackson & Raymond, 2006) are protected to some degree from the AB as their identification is less impaired than similar but less familiar stimuli. Smith, Most, Newsome, and Zald (2006) also showed that a stimulus recently associated with an aversive burst of white noise can automatically induce an AB-like impairment when used as a distractor in an RSVP task.…”
Section: The Attentional Blinkmentioning
confidence: 99%
“…Bruce concluded that facial identification and other perceptual assessments of faces can occur in parallel. Finally, using the AB paradigm, Awh et al (2004) observed a result opposite to that of Jackson and Raymond (2006)-no AB effect from unfamiliar T2 faceseven when the same T1 task (digit discrimination) produced an AB effect on a letter discrimination T2 task. The absence of an AB effect for unfamiliar T2 faces suggests that facial identification does not require the specific attentional resources required to perceive and encode T1.…”
mentioning
confidence: 92%
“…This result suggests that, with divided attention, facial identification is incomplete. Similarly, Jackson and Raymond (2006) used the attentional blink (AB) paradigm 2 to investigate the interaction between attention and facial identification. They found an AB effect when the faces (T2) were unfamiliar to participants, but not when the faces were familiar.…”
mentioning
confidence: 99%